Sacubitril/Valsartan: The Role of Neprilysin Pathway in Heart Failure - Sidhi L. Purwowiyoto; Ferina Angelia; Ananta S. Prawara (Universitas Padjadjaran, 2021)
Neprilysin (NEP) is an enzyme present in several body cells and is involved in the degradation of natriuretic peptides (NPs), bradykinin (BK), and adrenomedullin (ADM). Furthermore, sacubitril/valsartan (LCZ696), the first agent of Angiotensin Receptor Neprilysin Inhibitor (ARNI), has been developed to inhibit both Renin Angiotensin Aldosterone System (RAAS) and NEP. This study, therefore, aimed to discuss the role of sacubitril/valsartan in inhibiting the progression of heart failure (HF) by influencing the RAAS and NEP pathways. Data on previous articles related to basic theory and clinical trials of ARNI were collected through multiple search engines using the inclusion criteria: articles published in the English language within 2010 to 2020, while additional information on HF guidelines, RAAS, NPs, and ADM were acquired separately. Subsequently, a total of 30 studies were selected and further discussed. According to the results, NEP inhibition leads to a rise in the level of vasodilator agents and is beneficial for HF patients previously prescribed solely RAAS inhibiting agent (Angiotensin Converting Enzyme, ACE-inhibitor and Angiotensin II Receptor Blockers, ARB). In addition, the RAAS, as well as the NEP pathways play a significant role in HF progression and are inhibited by sacubitril/valsartan. Also, clinical trials showed sacubitril/valsartan is superior to ACE-inhibitor and ARB in clinical trials in treating, as well as reducing the morbidity and mortality rates of patients suffering from HF with reduced ejection fraction (HFrEF). Keywords: ARNI, heart failure, neprilysin, sacubitril/valsartan Sacubitril/Valsartan: Peran dari Jalur Neprilisin dalam Gagal JantungAbstrakNeprilisin (NEP) merupakan sebuah enzim yang dapat ditemukan di berbagai sel pada tubuh dan terlibat dalam mendegradasi peptida natriuretik, bradykinin (BK), dan adrenomedullin (ADM). Sacubitril/valsartan (LCZ696) merupakan agen pertama dari Angiotensin Receptor Neprilysin Inhibitor (ARNI) yang dikembangkan untuk menghambat jalur Renin Angiotensin Aldosterone System (RAAS) dan NEP. Review ini bertujuan untuk membahas peranan dari sacubitril/valsartan dalam menghambat progresi gagal jantung dengan memengaruhi jalur RAAS dan NEP. Pengumpulan data untuk teori dasar dan uji klinis ARNI dalam artikel review ini menggunakan beberapa mesin pencari. Informasi tambahan seperti pedoman-pedoman gagal jantung, RAAS, peptida natriuretik, dan ADM didapatkan secara terpisah. Kriteria inklusi yang digunakan adalah studi harus berbahasa Inggris dan dipublikasikan antara 2010 dan 2020. Sebanyak 30 studi diinklusi dan dibahas lebih lanjut dalam review ini. Hasilnya didapatkan bahwa inhibisi dari NEP menyebabkan terjadinya peningkatan agen-agen vasodilator yang berdampak positif bagi pasien gagal jantung yang sebelumnya direkomendasikan meminum obat yang hanya menghambat RAAS (penghambat Angiotensin Converting Enzyme/ACE dan Angiotensin II Receptor Blockers/ARB). Sacubitril/valsartan menghambat alur RAAS dan NEP yang mana keduanya memainkan peranan penting dalam progresi gagal jantung. Sacubitril/valsartan lebih superior dalam mencapai target pengobatan pasien yaitu mengurangi morbiditas dan mortalitas pasien gagal jantung dengan penurunan fraksi ejeksi dibandingkan dengan penghambat ACE dan ARB pada uji-uji klinis.Kata kunci: ARNI, gagal jantung, neprilisin, sacubitril/valsartan